UJI POTENSI BAKTERI ENDOFIT DARI DAGING BUAH SALAK PONDOH (Salacca edulis) DAN SALAK PADANGSIDEMPUAN (Salacca sumatrana) DALAM MENGHAMBAT PERTUMBUHAN Escherichia coli - Rizki Amelia Nasution; Ulfayani Mayasari (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Salak is a fruit that contains various health benefits, including the flesh of the fruit which contains bioactive compounds. Taking bioactive compounds directly from the flesh of the salak fruit will require quite a lot of biomass. Obtaining these bioactive compounds can be streamlined by using endophytic bacteria. Endophytic bacteria able to produce compounds of Â antibacterial. The aimed of this study to examine the antibacterial potential of Â endophytic bacteria derived from the flesh of the Pondoh and Padangsidempuan salak fruit against pathogenic bacteria, namely Escherichia coli. Method this studies is a laboratory experiment. A total of 10 isolates consisting of 6 isolates of Pondoh salak and 4 isolates of Padangsidempuan salak used were the results of isolation from salak fruit flesh in previous studies. Based on the results of the study, ten isolates indicate of antimicrobial activity to Escherichia coli. The inhibition zone diameter of highest value was owned by SP4 isolate, which was 1.1 mm. These results indicate that endophytic bacteria from the pulp of Pondoh and Padangsidempuan salak possess the potential to produce antibacterial compounds against gram-negative pathogenic bacteria, namely Escherichia coli.Â